Safety and immunogenicity of Vi-diphtheria toxoid typhoid conjugate vaccine among children below 2 years: a systematic review and meta-analysis - Mohamed Taha, Amira; Abouelmagd, Khaled; Mahmoud, Abdelrahman Mohamed; Elkasaby, Mohamed Hamouda; Nguyen, Dang; Ahmed, Ryan; Patel, Pari; Bonilla-Aldana, D. Katterine; Luna, Camila; Rodriguez-Morales, Alfonso J. (Frontiers in Microbiology, 2024)
The Vi-diphtheria toxoid typhoid conjugate vaccine (Vi-DT) has shown promising results in preventing typhoid fever in children under two years of age. However, a thorough assessment of its safety and immunogenicity is required to inform vaccination strategies. This systematic review and meta-analysis aimed to determine the safety and immunogenicity of Vi-DT in children below two years.We systematically searched multiple databases, including PubMed, Web of Science, and Scopus, for relevant studies published up to September 2023. We included studies reporting on the safety and immunogenicity outcomes of Vi-DT compared to the control or Vi-tetanus toxoid conjugated vaccine (Vi-TT) in children below two years. We applied a random-effects model for meta-analysis using RevMan 5.4.We expressed the results as risk ratio (RR) with a 95% confidence interval (95%CI).Results: In this analysis, five studies were selected, encompassing 1,292 children under two years who received the Vi-DT vaccine. No significant difference in immediate reactions was observed within 30 minutes post-vaccination between Vi-DT and control groups (RR: 0.99 [95% CI: 0.19, 5.26]), nor between Vi-DT and Vi-TT groups. For solicited adverse events within four weeks, the VI-DT group showed no significant increase in adverse events compared to control (RR: 0.93 [95% CI: 0.78, 1.12]) or Vi-TT (RR: 0.86 [95% CI: 0.69, 1.07]). Similarly, within seven days post-vaccination, risk ratios indicated no significant differences in adverse events between the groups. The 4-week seroconversion rate was significantly higher in the Vi-DT group compared to the control (RR: 1.99 [95% CI: 1.07, 3.69]), but no difference was found between Vi-DT and Vi-TT. Adverse events associated with typhoid conjugate vaccines were predominantly non-serious, including fever and injection site reactions. Serious adverse events were rare but included conditions like pneumonia and gastroenteritis.This meta-analysis highlights Vi-DT safety and immunogenicity in six to 24-month-old children. The findings support the use of this Vi-DT to expand typhoid vaccination in endemic regions, in line with WHO's strategy.